The Neo-Impressionist Portrait, 1886-1904 - Block, Jane.; Lee, Ellen Wardwell; ING Cultuurcentrum; Indianapolis Museum of Art. (Indianapolis : Indianapolis Museum of Art, 2014)
"Neo-Impressionism, the style pioneered by Georges Seurat (1859-1891), has long been associated with exquisite landscapes and intriguing scenes of urban leisure. Yet the movement's use of dotted brushwork and color theory also produced arresting portraits of unusual beauty and perception. The Neo-Impressionist Portrait is the first book to examine the astonishing portraits produced by the most important figures of Neo-Impressionism, including Seurat himself, Henri-Edmond Cross, Georges Lemmen, Maximilien Lu
"Published on the occasion of the exhibition Face to Face: Neo-Impressionist Portraits, 1886-1904. ING Cultural Centre, Brussels, February 19-May 18, 2014, Indianapolis Museum of Art, June 13-September 7, 2014."
Includes bibliographical references and index.
Keywords: Portrait painting, French -- 19th century -- Exhibitions; Portrait painting, Belgian -- 19th century -- Exhibitions; Neo-impressionism (Art) -- Exhibitions; Bildnisgraphik; Bildnismalerei; Neoimpressionismus; Neo-impressionism (Art); Portrait painting, Belgian; Portrait painting, French; 1800 - 1899; Exhibition catalogs